Oxygen and Carbon Isotope Trends in a Late Glacial-Holocene Pollen Site in Wyoming, U.S.A. - Gennett, Judith; Grossman, Ethan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTStable isotope studies of North American Late Glacial and Holocene lake sediments are few. Previous studies of pollen sites in Indiana, South Dakota, and the Great Lakes area show low δ18O values during deglaciation, rising to a Hypsithermal peak, and provide paleoenvironmental reconstructions similar to those obtained from pollen studies. Blacktail Pond, located in Douglas fir steppe in northern Yellowstone National Park, Wyoming, is one of the highest elevation lakes (2018 m) yet studied with both pollen and stable isotopes. Analyses of marls yield low oxygen and carbon isotope values at the base of the core probably due to meltwater influx at 12,500 to 14,000 BP. Tundra vegetation persisted for about an additional 1,500 years following the end of meltwater input. Later, more enriched isotope values fluctuate due to the high sensitivity of Blacktail Pond to evaporation and CO2 exchange because of its shallow depth. These processes result in a covariance between δ13C and δ18O related to the residence time of water in the pond; they exert a primary control on the isotopic composition of the Holocene marl. It may be possible to filter the data for residence time effects and extract additional paleoenvironmental information based on the offsets of isotopic data from the δ13C-δ18O trend for a particular pollen zone.